Management of Insect Pests with Bt Crops in the United States - Aaron J. Gassmann; Dominic Reisig (2022)
Genetically engineered corn and cotton that produce insecticidal toxins derived from the bacterium Bacillus thuringiensis (Bt) have been used to manage insect pests in the United States and elsewhere. In some cases, this has led to regional suppression of pest populations and pest eradication within the United States, and these outcomes were associated with reductions in conventional insecticides and increased profits for farmers. In other instances, pests evolved resistance to multiple Bt traits, compromising the capacity of Bt crops to manage pests and leading to increased feeding injury to crops in the field. Several aspects of pest biology and pest-crop interactions were associated with cases where pests remained susceptible versus instances where pests evolved resistance. The viability of future transgenic traits can be improved by learning from these past outcomes. In particular, efforts should be made to delay resistance by increasing the prevalence of refuges and using integrated pest management.